Validating a Multi-Level Succession Planning Framework: A Pilot Study on IT Companies in Pune (International Journal of Food and Nutritional Sciences, 2022)
The rapid expansion of the information technology sector in Pune has created unprecedented demands for effective succession planning mechanisms to ensure leadership continuity and organizational sustainability. This pilot study validates a multi-level succession planning framework through an empirical investigation of 104 respondents from lower, middle, and top management levels across IT companies operating within Pune city limits. The research employs quantitative methodology utilizing structured questionnaires, incorporating both demographic profiling and Likert-scale measurements to assess succession planning practices and their correlation with organizational performance indicators. Data analysis through one-sample t-tests and correlation analysis revealed statistically significant findings supporting the effectiveness of integrated succession planning frameworks. Results indicated that organizations with clearly defined succession planning mechanisms demonstrated higher employee engagement levels (r = 0.672, p < 0.001) and improved organizational performance metrics. The study identifies critical components including leadership identification processes, talent pool management, and strategic integration as fundamental elements of successful succession frameworks. Implications suggest that IT organizations must adopt comprehensive, multi-level approaches encompassing tactical knowledge transfer, leadership development programs, and performance management systems to address emerging challenges posed by rapid technological evolution and demographic shifts. Future research should explore longitudinal impacts of succession planning interventions and examine sector-specific modifications required for optimal framework implementation in diverse organizational contexts.